KAN-IKAN AIR TAWAR DARI SUNGAI UKAI, ANAK SUNGAI SIAK, RIAU - Chaidir P Pulungan (Berkala Perikanan Terubuk, 2011)
Collection of fishes from the Ukai stream, a branch of Siak River has been conductedfrom June to October 2008. Thirty one species that are belonged to 4 orders, 13 familiesand 25 generas are captured . The fish fauna was dominated by fish species that arebelonged to family Cyprinidae (45,16 %). Fish species that are abundance in the streamare Rasbora caudimaculata and Dermogenys sumatrana. Both species are found in theupstream. Fishes that are present in the stream mostly categorized as the primary family.In the Sumatra island, there are 25 fish families that are categorized as primary family.The number of primary family fishes present in the Ukai stream is 10 or 40% of that ofthe Sumatra’s. Almost all of fish species are belonged economical valued fishes.